Case report of a posterior vaginal wall Mullerian cyst - Kasioni, Spyridoula P.; Thesalokinefs, Panagiotis N.; Gialelis, Ioannis V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Mullerian cysts are common types of vaginal cysts, which are small and mainly asymptomatic. Sometimes they present as large symptomatic cystic lesions arising issues of differential diagnosis. They are congenital cysts found anywhere along the length of development of Mullerian duct, occurring typically during the conventional gynaecological examination. Authors report of a premenopausal woman presenting with a small asymptomatic, palpable cystic lesion in the posterior vaginal wall, found during the gynaecological re-examination one month after an open surgery for an ovarian endometrioma excision. The whole lesion was 0.4cm and surgically excised under general anesthesia. Postoperative period was completely uncomplicated. Pathology affirmed a benign Mullerian cyst. Although the majority of vaginal cysts may be asymptomatic, a complete excision is required especially in cases of suspected malignancy or other pathology. Clinical examination and imaging are not enough for determining the pathology and a histopathology confirmation is always necessary.